2016
DOI: 10.1016/j.psychres.2016.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Do bipolar subjects' responses to personality questionnaires lack reliability? Evidence from the PsyCoLaus study

Abstract: Differences in personality scores between subjects with and without mood disorders might result from response biases rather than specific personality traits per se. The aim of this study was to compare subjects with bipolar disorders (BPD) to non-bipolar subjects in terms of response quality to the NEO-FFI. Using data from the population-based cohort study PsyCoLaus, subjects were compared in terms of responses to the NEO-FFI, and indices of response quality were calculated. Hierarchical regression analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Thus, the purpose of this study was to measure whether each index was able to detect such response sets under controlled conditions. The present study was based on data from a group of 1,981 respondents who completed a personality questionnaire within a larger study (Dupuis et al, 2016). This sample was used for the present study because it is highly representative of high-quality surveys and was subject to frequent issues inherent in such studies, such as participants whose motivation waned in the course of responding, or those whose native language was not that of the questionnaires.…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the purpose of this study was to measure whether each index was able to detect such response sets under controlled conditions. The present study was based on data from a group of 1,981 respondents who completed a personality questionnaire within a larger study (Dupuis et al, 2016). This sample was used for the present study because it is highly representative of high-quality surveys and was subject to frequent issues inherent in such studies, such as participants whose motivation waned in the course of responding, or those whose native language was not that of the questionnaires.…”
Section: Data Sourcesmentioning
confidence: 99%
“…The sample consisted of adults who participated in a population study on cardiovascular health. Some respondents demonstrated careless responding (Dupuis et al, 2016), which proved suitable for testing whether they would have been identified as human, had this questionnaire been completed online.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Years of education 12.4 (3.3) 11.5 (3.4) 11.4 (2.6) 10.3 a (2. Analogous results, with evidence of a profile of high neuroticism and low extraversion and conscientiousness, have been noted in individuals with anxiety (Rosellini & Brown, 2011), depression (Hayward, Taylor, Smoski, Steffens, & Payne, 2013), bipolar disorder (Dupuis et al, 2016), schizophrenia (Gurrera, Nestor, & O'Donnell, 2000), psychosis (Lysaker & Taylor, 2007), and those at clinical high risk for psychosis (Marshall et al, 2012). Moreover, these findings have been replicated longitudinally for schizophrenia (Boyette, Nederlof, Meijer, De Boer, & De Haan, 2015) and depression (Hakulinen et al, 2015) showing stability on the traits despite symptom fluctuation.…”
Section: Discussionmentioning
confidence: 54%
“…It has been reported that in those who experience a depressive episode both in major depression and bipolar disorder there is evidence of an increase in neuroticism and a decrease in extraversion and conscientiousness (Harkness, Bagby, Joffe, & Levitt, 2002;Karsten et al, 2012). A similar pattern of personality traits has been observed in individuals with bipolar disorder who may present with high neuroticism and openness, and lower scores in extraversion, agreeableness, and conscientiousness (Antypa & Serretti, 2014;Dupuis et al, 2016).…”
Section: Introductionmentioning
confidence: 76%
“…This may lead to low validity of many questionnaires, as validity scales often do not represent a suffi cient assessment of a truthful answer to the questionnaire. These arguments sometimes lead to questioning the use of this method, especially in the cases of individuals who are not fully cognitively, socially, or medically eligible, and in individuals who do not cooperate or have some reason to infl uence the results [6][7][8][9][10][11][12]. Therefore, the combination of the questionnaire with other methods is suggested.…”
Section: Introductionmentioning
confidence: 99%